Patients’ perspectives on cancer care disparities in Central and Eastern European countries: experiencing taboos, misinformation and barriers in the healthcare system - Coppini, Veronica; Ferraris, Giulia; Ferrari, Maria Vittoria; Dahò, Margherita; Kirac, Iva; Renko, Ira; Monzani, Dario; Grasso, Roberto; Pravettoni, Gabriella (Frontiers in Oncology, 2024)
Introduction: Despite the advancements in oncological medicine and research, cancer remains the second leading cause of death in Europe with Central and Eastern European countries, such as Slovakia and Croatia, showing the highest mortality rates and disparities in access to appropriate and comprehensive cancer care. Therefore, the primary aim of the current study is to investigate cancer patients' perspectives and experiences to understand the possible underlying reasons for cancer disparities.Methods: Croatian cancer patients (n=15) and Slovak patients (n=11) were recruited through social media platforms, patients' organisations, and hospital websites and offered participation in online focus group discussions on perceived disparities, barriers or malfunctioning during and after their cancer journey. Transcripts of video and audio recordings of the interviews were translated and analysed using Thematic analysis.Results: Six Croatian and five Slovak themes emerged from the focus group discussions highlighting encountered barriers and perceived disparities, as well as suggestions or unmet needs. Most of the themes are common to both groups, such as the lack of information and use of the internet, and the taboos regarding cancer or psycho-oncological support. However, some themes are specific to each group, for instance, Slovak cancer patients remarked the fact that they do not mind travelling to get treatment as long as they can be treated in the west of Slovakia, while Croatian patients highlighted the need for more information after the illness and the socioeconomic impact financial constraints deriving from a cancer diagnosis.Discussion: Urgent intervention is needed in addressing disparities in Central and Eastern Europe. Present results could inform dedicated guidelines or better resource allocation strategies to reduce disparities in cancer care and promote inclusive healthcare.